Rancang Bangun Sistem Kontrol Kelembapan Media Pada Budidaya Cacing Tanah - Muhammad Zulkarnain (Politeknik Negeri Malang, 2019)
An important factor in worm cultivation is the humidity of the media, in practice for breedersthe worm regulates the humidity of the media by feeling the moisture with your hands, then when you feel it is dry then it is doused with water. In this study, a system will be made to determine the conditions of air temperature, air humidity, soil moisture, and soil pH in the worm habitat. Besides that, it also has an actuator as an automatic sprinkler when the humidity is dry. Monitoring results will be sent via the website. From the results of the research for 30 days, it was found that the humidity value at the node with the automatic sprinkler actuator had a more stable and optimal level of media humidity compared to conventional methods with a 10% difference in value. Meanwhile, the temperature and pH values ??tend to be the same. The yield on beds without actuators is 0.8 kg, while in beds with actuators it is 1.1 kg.